1983
DOI: 10.1152/ajprenal.1983.244.5.f526
|View full text |Cite
|
Sign up to set email alerts
|

Segmental effects of norepinephrine and angiotensin II on isolated renal microvessels

Abstract: Interlobular arteries and superficial afferent and efferent arterioles were isolated from rabbit kidney, and the effects of intraluminal pressure, norepinephrine (NE), and angiotensin II (ANG II) on lumen diameter were examined. A single microvessel was dissected and one end was cannulated. The other end of the vessel was occluded and lumen diameter was measured at fixed intraluminal pressures. With step increases in intraluminal pressure over the range of 70-180 mmHg, lumen diameters of the interlobular arter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
114
1
2

Year Published

1989
1989
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(132 citation statements)
references
References 24 publications
15
114
1
2
Order By: Relevance
“…Many authors suggested that anti hype rten sive agents such as ACE in hibitors, which reduce glomerular capillary hydraulic pressure, improve proteinuria and glomerular sclerosis (18,(20)(21)(22)(23). On the other hand, it has been reported that Ca-channel blockers show more selective relaxation of renal afferent arterioles than renal efferent arterioles (24,25).…”
Section: Methodsmentioning
confidence: 99%
“…Many authors suggested that anti hype rten sive agents such as ACE in hibitors, which reduce glomerular capillary hydraulic pressure, improve proteinuria and glomerular sclerosis (18,(20)(21)(22)(23). On the other hand, it has been reported that Ca-channel blockers show more selective relaxation of renal afferent arterioles than renal efferent arterioles (24,25).…”
Section: Methodsmentioning
confidence: 99%
“…The glomerular capillary pressure is profoundly affected by afferent and efferent arteriolar conditions, notably their conductance and relative pressures. These are controlled by tubuloglomerular feedback (TGF) and angiotensin II (AII) (Edwards 1983), respectively, and by α 1 ‐adrenergic activity in both zones (Zimmerman et al. 1984; Kon 1989).…”
Section: Curve Fittingmentioning
confidence: 99%
“…Therefore, mammals must maintain a constant GFRregardless of an extracellular fluid (ECF) volume status in order to rid the body of toxic wastes. Ang II contributes to these features of mammalian kidneys through its constrictive action on renal arteries (20)(21)(22) and its regulatory effect on iron transports (23)(24)(25). Recently, Okubo et al (26) and Kihara et al (27) reported that Agt-I-mice have severely impaired ability for urinary concentration during experimental ECF volume depletion.…”
Section: Rasis a Regulator Of Fluid Balancementioning
confidence: 99%